Understanding Coastal Citizens Perception on Urban Green Spaces: Evidence from Benin Republic in West Africa - Djikpo, V. A. Rosos; Teka, Oscar; Djossa, A. Bruno; Oumorou, Madjidou; Sinsin, Brice (European Scientific Journal, ESJ, 2022)
Urban Green Spaces (UGS) have several benefits for humans and environment. Despite these numerous benefits and important roles, UGS are often disregarded because their ecosystem services are not quantified and well-understood in developing countries. Until now, no study was carried out regarding the local perception, urban green spaces use values, threats and management strategies in Benin. This study was undertaken to assess the importance of UGS to citizens’ communities, to identify threats to viability and communities’ commitment or willing to adhere participatory suitable management in three cities (Ouidah, Cotonou and Porto-Novo) located in the coastal area of Benin. Surveys were conducted with a questionnaire and respondent were selected randomly in communities. A total of 360 informants were selected, 120 per district (40 users, 40 household and 40 key informants). The survey assessed residents’ perception of UGS with reference to key socioeconomic variables (age, gender, educational levels). Data were analyzed using Chi-square test, chordDiagram, correlations through corrplot packages and Principal Component Analysis under R software. It came out from this study, six positive aspects: shading, air pollutants absorption, aesthetics, recreation, medicinal uses and economic benefit and four incivility or negative aspects: waste dump, mosquito lodges, threat to roads and buildings cracking with roots. These benefits and disturbance inputted to trees differed significantly between the three cities (χ2 = 110.65; P <0.001) and three categories of interviewees (χ2 = 25.32; P = 0.004). Urban green spaces were also subject to anarchic exploitation which consisted of illegal logging, debarking, pruning, topping and root harvesting. This study allowed concluding that UGS plays an important socioeconomic role for surrounding communities. Therefore, it seems urgent to ensure the viability of these ecosystems. It also reported that communities expressed their will to participate in UGS protection and conservation.